Peran Sastra Dalam Pembelajaran Bahasa Indonesia - Yustika Sari (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The focus of the discussion in this research regarding the role of literature in learning Indonesian and the importance of reading literary works in developing language skills can provide a deep understanding of how literature influences students' learning processes. The integration of literature in Indonesian language learning is still less than optimal. Therefore, efforts need to be made to optimize the role of literature. By optimizing the role of literature, it is hoped that learning Indonesian can provide maximum benefits for students. In this research, the author used a qualitative method through literature study. Literature has a significant role in learning Indonesian. Literary works can be used as a medium to develop language skills (listening, reading, writing, speaking), enrich vocabulary, understand grammar, and increase appreciation of literary works. Apart from that, literary learning also plays a role in instilling life values, building character, encouraging creativity, and increasing awareness of culture and diversity. Literature also encourages students' creativity and critical thinking, literature learning allows students to express their feelings about beautiful things.